2011
DOI: 10.4103/0019-509x.82874
|View full text |Cite
|
Sign up to set email alerts
|

Management of primary and metastatic triple negative breast cancer: Perceptions of oncologists from India

Abstract: This data offers insight into the perceptions and practice of a diverse cross-section of practicing oncologists in India with respect to their therapeutic choices in metastatic and adjuvant settings in triple negative breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Our estimated median OS for luminal A, luminal B, HER2-enriched, and TNBC (41, 27, 26, and 19 months, respectively) is consistent with published estimates. 21 , 43 , 44 Studies by Khadkban et al 43 and Parikh et al 44 reported OS ranging from 21.2 to 31.4 months and 9 to 22 months, respectively, while Gogia et al 21 reported separate survival rates with respect to different types of molecular subtypes, ranging from 17.5 (95% CI, 11 to 19.2) months to 41.4 (95% CI, 30 to 52.8). Our results align closely with this real-world evidence in the Indian context (Fig 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our estimated median OS for luminal A, luminal B, HER2-enriched, and TNBC (41, 27, 26, and 19 months, respectively) is consistent with published estimates. 21 , 43 , 44 Studies by Khadkban et al 43 and Parikh et al 44 reported OS ranging from 21.2 to 31.4 months and 9 to 22 months, respectively, while Gogia et al 21 reported separate survival rates with respect to different types of molecular subtypes, ranging from 17.5 (95% CI, 11 to 19.2) months to 41.4 (95% CI, 30 to 52.8). Our results align closely with this real-world evidence in the Indian context (Fig 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…[8] TNBC is said to be a disease with poor prognosis, suboptimal response to therapy and therefore is a disease with unmet needs. [9][10][11] Various biomarkers such as circulating tumor cells, cell-free DNA, and PD-L1 expression as well as novel therapeutic agents have been studied. [12][13][14][15] Till they become standard of care, is there a way of improving the survival in patients with TNBC?…”
Section: Discussionmentioning
confidence: 99%
“…The gene mutation may originate from the maternal or the paternal side, and each offspring of a BRCA carrier has a 50% chance of inheriting the mutation. [ 34 35 ]…”
Section: Discussionmentioning
confidence: 99%